1998
DOI: 10.1002/(sici)1097-0282(199603)38:3<329::aid-bip6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

A vibrational spectroscopic study of the metastable form of associated polyinosinic acid

Abstract: We have studied by Raman and ir spectroscopy the metastable complex formed by the self‐association of polyinosinic acid in aqueous solution. The complex is easily prepared by quickly cooling to ca. 0°C a warm solution of the polyribonucleotide to which a small amount of rubidium salt has been added. Upon heating, this metastable form melts cooperatively near 13°C, well below the dissociation temperature of a stable four‐stranded complex, which occurs at 47°C in the same conditions. The presence of several comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…8 Further Raman IR spectroscopic measurements pointed out that the sugar pucker might be a mixture of C2′/C3′-endo conformations. 11,12 Recent biochemical research indicated that purinerich regions containing adenine bases play an important role in cellular processes. For instance, the fragile X mental retardation protein binds specifically to a purine-rich fragment containing both guanine and adenine in its mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…8 Further Raman IR spectroscopic measurements pointed out that the sugar pucker might be a mixture of C2′/C3′-endo conformations. 11,12 Recent biochemical research indicated that purinerich regions containing adenine bases play an important role in cellular processes. For instance, the fragile X mental retardation protein binds specifically to a purine-rich fragment containing both guanine and adenine in its mRNA.…”
Section: Introductionmentioning
confidence: 99%